Surviving COVID-19 and Ensuring Digital Access to Education in Extreme Poverty Contexts - Ruiz-Román, Cristóbal; Juárez-Pérez-Cea, Jesús; Molina-Cuesta, Lorena; Azorín, Cecilia (My University, 2021)
The pandemic has highlighted disparities in access to technology. There is no doubt that many children and young people without physical contact to schools and no technological devices at home have fallen into the digital gap, and into social inequality. According to Harris (2020, 3): These current circumstances demand that all students have Internet connectivity so that they can access resources and continue progressing. Those leading education systems, therefore, have a moral duty to invest in connectivity for all learners, as a priority, if learning is to be genuinely inclusive and equity is to be realised. Hence, accepting educational responsibility is essential for survival in the Era of COVID-19. The paper focuses on the digital divide in “Los Asperones” (Alcalde, Ruiz-Román and Molina, 2017), a disadvantaged area of Malaga (southern Spain), where there are 1000 people located there, of which 90% are in extreme poverty. According to Ruiz-Román, Molina and Alcaide (2018) in recent years there has been a huge effort on the part of educational institutions and NGOs to get children and young people to advance in their studies. Azorín (2020) and Herrera-Pastor, Juárez and Ruiz-Román (2020) note that Los Asperones survives thanks to a social network that revolves around this neighborhood, but COVID-19 has undoubtedly made the social and exclusion gap even wider. A patronage project led by the University of Malaga (UMA) and the Association “Chavorrillos” is currently under way in response to the crisis. The project aims to generate synergies between volunteers from the UMA and the neighborhood, thus empowering the people who live Los Asperones, and seeks to combat inequality and the digital divide by providing tools that truly allow "connect to learn: learn to connect”
Keywords: Educación social; Pobreza; Social Education; Poverty